PASTA kinase signaling regulates peptidoglycan synthesis in Enterococcus faecalis by direct inhibition of UDP-N-acetylglucosamine 1-carboxyvinyl transferase activity - Carly A. Mascari; Dušanka Djorić; Christopher J. Kristich (mBio)
ABSTRACT Proper control of bacterial peptidoglycan (PG) synthesis is critical to balance growth, cell division, and stress responses with other energetic needs of the cell. The first committed step of the PG biosynthetic pathway is catalyzed by UDP-N-acetylglucosamine 1-carboxyvinyl transferases (UNAG-CTases). The genomes of most Firmicutes encode two UNAG-CTase homologs: MurAA (or MurA/MurA1) and MurAB (or MurZ/MurA2). The primary UNAG-CTase in many Firmicutes (MurAA) is regulated by proteolysis in response to signals sensed by transmembrane kinases containing PASTA domains through the action of the kinase substrate IreB, impacting the amount and/or rate of PG synthesis. However, the secondary UNAG-CTases in Firmicutes do not appear to be controlled by proteolysis, and their regulation remains unknown. We sought to determine if signaling via IreK, the PASTA kinase in the opportunistic pathogen Enterococcus faecalis, might also regulate PG synthesis by the secondary UNAG-CTase (MurAB). Using genetic and biochemical approaches, we found that IreK-mediated phosphorylation of IreB was essential in the absence of MurAA, confirming that IreB regulates additional targets beyond MurAA. We demonstrated that the secondary UNAG-CTase, MurAB, is one such target and that IreB directly regulates the catalytic activity of MurAB via phosphorylation-modulated direct physical interaction to impact PG synthesis in E. faecalis. Hence, our work establishes not only a new regulatory target for the IreK-IreB signaling axis and a new mechanism of action for IreB but also the first described regulatory mechanism for a MurAB homolog in any organism, a mechanism that is distinct from the established paradigm for the primary UNAG-CTases.IMPORTANCEPeptidoglycan (PG) is a critical mesh-like polymer that provides osmotic support and structure to the bacterial cell wall, and regulation of its synthesis is essential for proper cell growth, division, and stress responses. In Firmicutes, control of PG synthesis is known to occur through the regulation of the primary UNAG-CTase by proteolysis in response to signals mediated by the transmembrane PASTA kinase. Firmicutes also encode a secondary UNAG-CTase homolog whose regulation has remained unknown. Our results demonstrate a new mechanism for the regulation of PG synthesis in Firmicutes—direct inhibition of the enzymatic activity of the secondary UNAG-CTase by the PASTA kinase-IreB signaling axis via phosphorylation-modulated direct physical interaction between IreB and the secondary UNAG-CTase in Enterococcus faecalis.